The Effect of Bank Performance On Stock Returns: The Indonesian Case - Kartini Potoe; Nofal, Mohammad; Fattah, Vitayanti; Iskandar, Rizkiani (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effect of bank performance on stock returns of banking companies listed on the Indonesia Stock Exchange during 2021–2025. Using panel data from 35 banks selected through purposive sampling, the study employs a random-effects regression model. Bank performance is measured by Return on Assets (ROA), Return on Equity (ROE), Net Interest Margin (NIM), and Third-Party Funds (DPK). The results show that ROA has a significant negative effect on stock returns, while ROE has a significant positive effect. NIM and DPK have no significant effect. These findings imply that investors should prioritize ROE when evaluating banking stocks.